Twentieth-century warming preserved in a Geladaindong mountain ice core, central Tibetan Plateau - Yulan Zhang; Shichang Kang; Bjorn Grigholm; Yongjun Zhang; Susan Kaspari; Uwe Morgenstern; Jiawen Ren; Dahe Qin; Paul A. Mayewski; Qianggong Zhang; Zhiyuan Cong; Mika Sillanpää; et al. (Annals of Glaciology, 2016)
High-resolution δ18O records from a Geladaindong mountain ice core spanning the period 1477-1982 were used to investigate past temperature variations in the Yangtze River source region of the central Tibetan Plateau (TP). Annual ice-core δ18O records were positively correlated with temperature data from nearby meteorological stations, suggesting that the δ18O record represented the air temperature in the region. A generally increasing temperature trend over the past 500 years was identified, with amplified warming during the 20th century. A colder stage, spanning before the 1850s, was found to represent the Little Ice Age with colder periods occurring during the 1470s–1500s, 1580s–1660s, 1700s–20s and 1770s–1840s. Compared with other temperature records from the TP and the Northern Hemisphere, the Geladaindong ice-core record suggested that the regional climate of the central TP experienced a stronger warming trend during the 20th century than other regions. In addition, a positive relationship between the Geladaindong δ18 O values and the North Atlantic Oscillation index, combined with a wavelet analysis of δ18 O records, indicated that there was a potential atmospheric teleconnection between the North Atlantic and the central TP.